Personalization strategies in digital mental health interventions: a systematic review and conceptual framework for depressive symptoms - Hornstein, Silvan; Zantvoort, Kirsten; Lueken, Ulrike; Funk, Burkhardt; Hilbert, Kevin (Frontiers in Digital Health, 2023)
Personalization is a much-discussed approach to improve adherence and outcomes for Digital Mental Health interventions (DMHIs). Yet, major questions remain open, such as 1) what personalization is, 2) how prevalent it is in practice, and 3) what benefits it truly has. We address this gap by performing a systematic literature review identifying all empirical studies on DMHIs targeting depressive symptoms in adults from 2015 to September 2022. The search in Pubmed, SCOPUS, and Psycinfo led to the inclusion of 138 articles, describing 94 distinct DMHIs provided to an overall sample of approximately 24,300 individuals. Our investigation results in the conceptualization of personalization as purposefully designed variation between individuals in an intervention’s therapeutic elements or its structure. We propose to further differentiate personalization by what is personalized (i.e., intervention content, content order, level of guidance or communication) and the underlying mechanism (i.e., user choice, provider choice, decision rules, and machine-learning (ML) based approaches). Applying this concept, we identified personalization in 66% of the interventions for depressive symptoms, with personalized intervention content (32% of interventions) and communication with the user (30%) being particularly popular. Personalization via decision rules (48%) and user choice (36%) were the most used mechanisms, while the utilization of ML was rare (3%). Two-thirds of personalized interventions only tailored one dimension of the intervention. Therefore, we conclude that future interventions could provide even more personalized experiences and especially benefit from using ML models. Finally, empirical evidence for personalization was scarce and inconclusive, making further evidence for the benefits of personalization highly needed.